Association of major dietary patterns and blood pressure longitudinal change in Bangladesh. Issue 6 (June 2015) - Jiang, Jieying; Liu, Mengling; Parvez, Faruque; Wang, Binhuan; Wu, Fen; Eunus, Mahbub; Bangalore, Sripal; Ahmed, Alauddin; Islam, Tariqul; Rakibuz-Zaman, Muhammad; Hasan, Rabiul; Sarwar, Golam; et al.
<x xml:space="preserve">Abstract</x> Background: Observational studies and clinical trials have shown associations of diet and high blood pressure (BP). However, prospective studies on the association between dietary patterns and longitudinal BP change are lacking, especially in low-income populations. Method: We evaluated the association of dietary patterns and food groups with longitudinal change of BP in 10 389 participants in the Health Effects of Arsenic Longitudinal Study, with a median of 6.7 years of follow-up. Dietary information was obtained through a previously validated food-frequency questionnaire. BP was measured at baseline and at each biennial follow-up using the same method. Result: Each standard deviation (SD) increase for the 'gourd vegetable' dietary pattern score was related to a slower annual change of 0.08, 0.04, and 0.05 mmHg in SBP, DBP, or pulse pressure, respectively. Each SD increase in the 'balanced' dietary pattern score was related to a decreasing annual change of 0.06 mmHg (P = 0.012) and 0.08 mmHg in SBP and pulse pressure (P < 0.001). On the contrary, one SD increase in 'western' dietary pattern score was related to a greater annual increase of 0.07 (P = 0.005) and 0.05 mmHg in SBP and pulse pressure (P = 0.013). Higher intake of fruits and vegetables was associated with a slower rate of change in annual SBP and pulse pressure, whereas higher meat intake was related to a more rapid increase in annual pulse pressure. Conclusion: The findings suggest that dietary patterns play a significant role in the rate of BP change over time in a low-income population.